The effect of dialogue strategy on developing oral expression skills among first intermediate grade students - Ahmed, Biman Jalal (Al-Adab Journal, 2021)
The study aimed to find out the effect of the dialogue strategy on developing oral expression among first-grade intermediate students, and the research sample consisted of (66) students, the experimental group reached (34) students who studied using the dialogue strategy, and the control group reached (32) students who studied in the traditional way. The researcher prepared a test and scale for correcting the oral expression skills of the students, and the researcher used statistical methods represented in the arithmetic averages, the T test, and the standard deviation. The results also resulted in the existence of statistically significant differences between the experimental and control groups at the level of significance (0.05) and in favor of the experimental group in all skills. The researcher recommended focusing on oral expression skills and working on their development.